Application of the Make a Match Model in Learning Arabic Mufradat - Sekar Dwi Nur Aini; Nurfuadi Nurfuadi (Edumaspul: Jurnal Pendidikan, 2023)
Inlearning Arabic there are four abilities that must be learned and mastered by students, namely the ability to listen, speak, read and write. To master these four skills, one of the efforts that must be taken is to improve the acquisition of mufradat or Arabic vocabulary, because it is very helpful for the learning results of the four Arabic skills.This study aims to find out and analyze how the application of the Make A Match model in learning Arabic mufradat at MTs Muhammadiyah 09 Purbalingga. This research is a type of field research that is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results of this study show that mufrodat learning at MTs Muhammadiyah 09 Purbalingga, teachers conduct learning in three stages, namely the preparation, implementation and evaluation stages. Then in the implementation of mufradat learning the teacher uses the Make a Match model to help students understand and memorize the mufradat given. By using this model, it creates a pleasant learning atmosphere and makes students become more active when participating in learning activities..